2015
DOI: 10.1007/s00894-015-2773-3
|View full text |Cite
|
Sign up to set email alerts
|

Antiradical capacity of ommochromes

Abstract: Ommochromes are colored substances that apparently function as biological signals among arthropods and insects. These substances may prevent oxidative stress by scavenging free radicals. Two principal mechanisms exist for scavenging free radicals: the electron transfer and hydrogen atom transfer. In this investigation, a theoretical study of the antiradical capacity of five ommochromes was performed within the density functional theory framework. Vertical ionization energy and vertical electron affinity were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 39 publications
4
31
0
1
Order By: Relevance
“…This result is consistent with in silico measurements of hydrogen‐donor capacities of ommochromes (Fig. C) (Romero & Martínez, ; Zhuravlev et al, ). For xanthommatin, the three best H‐donor sites localise to the aspartyl chain while the two best ones of ommatin D are within the pyrido[a]phenoxazone system (Fig.…”
Section: Ommochrome Biochemistry: From the Indole To The Phenoxazone supporting
confidence: 90%
See 4 more Smart Citations
“…This result is consistent with in silico measurements of hydrogen‐donor capacities of ommochromes (Fig. C) (Romero & Martínez, ; Zhuravlev et al, ). For xanthommatin, the three best H‐donor sites localise to the aspartyl chain while the two best ones of ommatin D are within the pyrido[a]phenoxazone system (Fig.…”
Section: Ommochrome Biochemistry: From the Indole To The Phenoxazone supporting
confidence: 90%
“…It occurs because the electronic delocalisation of the phenoxazine chromophore is increased in H 2 ‐xanthommatin, leading to greater stabilisation by resonance of the oxonium ion (O + ) (Schäfer & Geyer, ). Recent studies suggested that these redox and related antiradical behaviours allow phenoxazine‐based compounds to buffer oxidative stress (Romero & Martínez, ; Farmer et al, ; Shah, Margison & Pratt, ). The theoretical basis of this putative biological role was modelled using computational and quantum chemistry, as well as in biological assays.…”
Section: Ommochrome Biochemistry: From the Indole To The Phenoxazone mentioning
confidence: 99%
See 3 more Smart Citations